O trabalho voluntário e a responsabilidade social empresarial: a expropriação do tempo livre como uma estratégia de envolvimento cooptado do trabalhador - CUNHA, Núbia Maria Dias da (2007)
It analyzes the voluntary work and the enterprise company social responsibility. It distinguishes the social responsibility in the basis of the capitalist reorganization movement, while being a strategy for the formation of the current relationship between capital and work, in which the voluntary work constitutes a resource for the capture of the laboring subjectivity, through the intensification of the cooperation of the worker with the company. This work focuses on the expropriation of free time by the capital as form of enrollment of the employee in the experiences of social responsibility and also as an involvement strategy to co-opt the worker to the demands of the actual productive rationality. The analysis of this tendency is accurately deepened in this researching paper based on empirical indications of the initiatives of voluntary work that have been implanted for the Aluminum Trust of the State of the Maranhão in the meshes of its politics of social responsibility. Yet, it analyzes the modalities of expropriation of free time conducted by the company that uses the voluntary work as an amplifying mechanism to the exploration and control of the work force and in the capture of the laboring assent to the current standard of production and work.